Advancing the Fight Against Cervical Cancer: The Promise of Therapeutic HPV Vaccines - Qian Zheng; Misi He; Zejia Mao; Yue Huang; Xiuying Li; Ling Long; Mingfang Guo; Dongling Zou (Vaccines, 2025)
Human papillomavirus (HPV) is a major global health issue and is recognized as the leading cause of cervical cancer. While prophylactic vaccination programs have led to substantial reductions in both HPV infection rates and cervical cancer incidence, considerable burdens of HPV-related diseases persist, particularly in developing countries with inadequate vaccine coverage and uptake. The development of therapeutic vaccines for HPV represents an emerging strategy that has the potential to bolster the fight against cervical cancer. Unlike current prophylactic vaccines designed to prevent new infections, therapeutic vaccines aim to eradicate or treat existing HPV infections, as well as HPV-associated precancers and cancers. This review focuses on clinical studies involving therapeutic HPV vaccines for cervical cancer, specifically in three key areas: the treatment of cervical intraepithelial neoplasia; the treatment of cervical cancer in combination with or without chemotherapy, radiotherapy, or immune checkpoint inhibitors; and the role of prophylaxis following completion of treatment. Currently, there are no approved therapeutic HPV vaccines worldwide; however, active progress is being made in clinical research and development using multiple platforms such as peptides, proteins, DNA, RNA, bacterial vectors, viral vectors, and cell-based, each offering relative advantages and limitations for delivering HPV antigens and generating targeted immune responses. We outline preferred vaccine parameters, including indications, target populations, safety considerations, efficacy considerations, and immunization strategies. Lastly, we emphasize that therapeutic vaccines for HPV that are currently under development could be an important new tool in fighting against cervical cancer.